Special Economic Zones in International Economic Law: Towards Unilateral Economic Law - Julien Chaisse (19418806) (2021)
The international economic regime has entered a new phase of reassertion of sovereignty by States. While States continue to show respect for the values of international (economic) law, the institutionalization of these values has devolved from the international (to the regional) to the domestic level of governance. A new form of ‘unilateral economic law’ is thus gaining importance in the development of international and domestic laws and institutions. However, it remains largely understudied. This article discusses the development and proliferation as well as the importance of special economic zones as a new form of unilateral economic law in the overall system of international economic law. This article identifies four types of economic unilateralism: classical unilateralism, embedded unilateralism, sustainability unilateralism, and national security unilateralism. The new special economic zone unilateralism represents a middle ground between the two extremes of unilateral liberalization and aggressive unilateralism. Accordingly, special economic zone unilateralism introduces a new layer in the overall system of international economic law. First, special economic zones embody a new compromise between the State and the market. The State-controlled promotion of trade and investment taking place through special economic zones represents a complex compromise between the liberalization and protection of economic sovereignty. Second, the spatiality of trade and investment promotion through special economic zones is different from that of international economic law. The liberalization of trade and investment does not take place for the whole country but for an isolated jurisdiction within the broader national jurisdiction, while the focus is on the supply side rather than the traditional input factors of production. Overall, the new special economic zone unilateralism provides insights into the future of international economic law as envisaged by States. Special economic zones have been employed by States both as an alternative and as a complement to trade and investment promotion through the instruments of international economic law. Other Information Published in: Journal of International Economic Law License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/jiel/jgab025